Composite positive plate and preparation method thereof
By coating layered oxides and polyanionic materials on the two plate surfaces of the mesh current collector, the problem of insufficient cycle life and specific capacity of the positive electrode material of sodium ion battery is solved, the battery performance and life are improved, and the resistance is reduced .
Patent Information
- Application Number
- CN202411284755.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-17
AI Technical Summary
Existing sodium ion battery positive electrode materials have shortcomings in terms of cycle life and specific capacity, especially the layered oxide structure has poor stability, the specific capacity of polyanionic materials, and Prussian blue compounds are prone to react with the electrolyte to cause corrosion, affecting the battery cell. performance.
By using the composite positive electrode sheet preparation method, layered oxides and polyanionic materials are coated on the two plate surfaces of the mesh current collector, the material contact area is increased by using the mesh current collector, and the coating density is regulated to avoid interface impedance and The coating material drop caused by differences in ductility improves battery performance.
It improves the anchoring force and adhesion force of the positive electrode material, fully utilizes the advantages of high specific capacity of layered oxides and long cycle life and safety of polyanionic materials, reduces the resistivity, and improves the battery capacity and rate performance. Extend battery life.
Smart Images

Figure CN119153628A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and more specifically, relates to a composite positive electrode sheet and a preparation method thereof. Background Art
[0002] Sodium-ion battery raw materials are abundant, with good availability and low cost, and have been used in large-scale energy storage, such as A00-class electric vehicles and power tools. The positive electrode materials of sodium-ion batteries mainly include layered oxides, polyanion compounds and Prussian blue compounds.
[0003] However, each of the above materials has its own advantages and disadvantages. Layered oxides have high specific capacity, but poor structural stability; polyanion compounds have long cycle life and outstanding cost and safety advantages, but low specific capacity; Prussian blue compounds have low cost and high specific capacity, but the material easily reacts with electrolyte components to generate hydrogen fluoride (HF), which corrodes the current collector in the positive electrode material; because Prussian blue compounds themselves contain crystalline water, they produce gas during the charging and discharging process. How to coordinate the design, make full use of the advantages of various materials, avoid disadvantages, and thus improve the quality of sodium-ion batteries has always been a difficult problem in the industry.
[0004] Patent CN114132971A proposed a multi-phase composite symbiotic structure, which solid-phase sintered 11 target components to obtain a multi-phase layered oxide with a P2-O3-P3 structure, replacing a single-phase positive electrode and significantly improving the cycle performance of the layered oxide. This method requires too many types of raw materials and a complicated preparation process.
[0005] Patent CN117497826A provides a composite battery cell with multiple positive electrode sheets, in which different types of positive electrode active materials are coated sequentially to form positive electrode sheets, and then different types of positive electrode sheets are combined to form a battery cell with high energy density and excellent cycle performance. However, sequential coating will cause the electrode sheets to produce a large interface impedance, which is not conducive to improving the performance of the battery cell.
[0006] Patent CN118335906A proposes a sodium ion positive electrode plate structure, including a current collector, a first electrode layer (O3 phase or P2 phase layer oxygen material) and a second electrode layer (polyanion material). After the first electrode layer is completely dried, the second electrode layer is coated on the first electrode layer, and the two electrode layers are located on the same side of the current collector. Since the second electrode layer cannot be fused with the first electrode layer, there will be an obvious interface between the two electrode layers. The materials on both sides of the interface are different. When the pole piece is rolled, due to the different compaction densities of the two electrode layers, the resulting extensions are different, and stress will be generated at the interface, causing the second pole piece layer to drop or even fall off. This situation will seriously reduce the peel strength of the pole piece and seriously affect the performance of the battery cell. In addition, due to the existence of the interface, during the charging and discharging process of the battery cell, the interface will produce a large impedance to the migration of electrons and ions, resulting in poor battery cell capacity and rate performance. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides a method for preparing a composite positive electrode sheet, comprising the following steps:
[0008] Step S1, preparing a positive electrode glue solution, wherein the mass ratio of N-methylpyrrolidone (NMP) to polyvinylidene fluoride (PVDF) in the positive electrode glue solution is (90-95): (5-10);
[0009] Step S2, preparing positive electrode slurry A, wherein the mass ratio of O3 layer oxygen material, polyvinylidene fluoride (PVDF), SP carbon black conductive agent, and carbon fiber conductive agent (VGCF) in the positive electrode slurry A is (93-95):3:(1-2):(1-2);
[0010] Step S3, preparing positive electrode slurry B, wherein the mass ratio of polyanion material composite sodium iron phosphate (NFPP), polyvinylidene fluoride (PVDF), SP carbon black conductive agent, and conductive agent 2-VGCF in the positive electrode slurry B is (90-95):3:(1-4):(1-3);
[0011] Step S4, positive electrode coating, coating the positive electrode slurry A on the first plate surface of the mesh current collector 1, drying to form a first coating 21; coating the positive electrode slurry B on the second plate surface of the mesh current collector 1, drying to form a second coating 22; rolling and stripping the coated positive electrode to form a composite positive electrode sheet 2.
[0012] As a preferred solution, the mesh current collector 1 is a mesh aluminum foil.
[0013] More specifically, the positive electrode paste in step S1 is prepared by the following steps:
[0014] Step S11, mixing N-methylpyrrolidone (NMP) and polyvinylidene fluoride (PVDF) in a mass ratio of (90-95): (5-10), and mixing them uniformly by stirring;
[0015] Step S12, scraping the PVDF adhered to the wall of the stirring tank and the stirring paddle into the solution by scraping the wall and the stirring paddle; and mixing evenly by stirring;
[0016] Step S13, vacuuming and stirring at the same time, controlling the viscosity of the glue solution to 1000mPa·s-4000mPa·s, and the solid content to 5%-10%, to prepare the positive electrode glue solution.
[0017] As a preferred solution, the stirring method in step S11 is a revolution speed of 10 rpm, a rotation speed of 500 rpm, and stirring for 15 minutes;
[0018] As a preferred solution, the stirring method in step S12 is a revolution speed of 20 rpm, a rotation speed of 1200 rpm to 1500 rpm, and stirring for 6 h to 12 h;
[0019] As a preferred solution, the stirring method in step S13 is a revolution speed of 10 rpm and a rotation speed of 500 rpm.
[0020] As a preferred solution, the vacuuming time in step S13 is 1 hour, and the vacuum degree is controlled to be less than -80 KPa.
[0021] As a preferred solution, in step S13, the glue solution 3 is transparent, without lumps or flocs.
[0022] More specifically, the positive electrode slurry A in step S2 is prepared by the following steps:
[0023] Step S21, adding the positive electrode glue prepared in step S1 into a homogenization tank, stirring for 30 minutes at a revolution speed of 10 rpm and a rotation speed of 500 rpm;
[0024] Step S22, adding SP carbon black conductive agent and carbon fiber conductive agent (VGCF) into a homogenization tank, stirring for 150 min to 180 min under the conditions of revolution speed of 15 rpm and rotation speed of 1800 rpm;
[0025] Step S23, adding O3 layer oxygen material into the homogenization tank;
[0026] Step S24, adding the positive electrode glue into the homogenization tank, making the mass ratio of O3 layer oxygen material, polyvinylidene fluoride (PVDF), SP carbon black conductive agent, and carbon fiber conductive agent (VGCF) be (93-95):3:(1-2):(1-2); stirring speed is 10 rpm for revolution, 500 rpm for rotation, and stirring time is 15 min;
[0027] Step S25, scraping the wall and the paddle to scrape the material stuck on the wall of the stirring tank and the stirring paddle into the solution;
[0028] Step S26, stirring for 180 min to 240 min under the conditions of revolution speed of 15 rpm and rotation speed of 1800 rpm;
[0029] Step S27, adding NMP to adjust the slurry viscosity to 4000mPa·s to 8000mPa·s, and the solid content ranges from 50% to 60%;
[0030] Step S28, evacuate to remove bubbles, evacuate to a vacuum degree of less than -80 KPa, stir for 30 minutes at a revolution speed of 10 rpm and a rotation speed of 500 rpm to obtain positive electrode slurry A.
[0031] More specifically, the positive electrode slurry B in step S3 is prepared by the following steps:
[0032] Step S31, adding the glue solution in step S1 into a homogenization tank, stirring for 30 minutes at a revolution speed of 10 rpm and a rotation speed of 500 rpm;
[0033] Step S32, adding SP carbon black conductive agent and carbon fiber conductive agent (VGCF) into a homogenization tank, stirring for 150 min to 180 min under the conditions of revolution speed of 15 rpm and rotation speed of 1800 rpm;
[0034] Step S33, adding composite sodium ferric phosphate (NFPP) into a homogenization tank;
[0035] Step S34, adding the glue solution in step S1 into a homogenization tank, stirring for 15 minutes at a revolution speed of 10 rpm and a rotation speed of 500 rpm;
[0036] Step S35, scraping the wall and the paddle to scrape the material stuck on the wall of the stirring tank and the stirring paddle into the solution;
[0037] Step S36, stirring for 180 min to 240 min under the conditions of revolution speed of 15 rpm and rotation speed of 1800 rpm;
[0038] Step S37, adding NMP to adjust the slurry viscosity to 5000mPa·s to 8000mPa·s, and the solid content to 50% to 60%;
[0039] Step S38, evacuate to remove bubbles, evacuate to a vacuum degree of less than -80 KPa, stir for 30 minutes at a revolution speed of 10 rpm and a rotation speed of 500 rpm to obtain positive electrode slurry B.
[0040] As a preferred solution, the mesh current collector 1 has a thickness of 8 μm to 17 μm, the mesh 11 of the mesh current collector 1 has a pore size of 5 μm to 10 μm, the mesh 11 depth is ≤ 1 / 3 of the mesh current collector thickness, and the mesh 11 spacing is > 20 μm;
[0041] As a preferred solution, the first coating 21 is 80 g / m 2 ~300g / m 2 ,
[0042] As a preferred solution, the thickness of the first coating 21 is 50 μm to 200 μm.
[0043] As a preferred solution, the surface density of the second coating 22 is 92 g / m 2 ~345g / m 2 ,
[0044] As a preferred solution, the ratio of the surface density of the first coating 21 to the surface density of the second coating 22 is 1:(1-1.15).
[0045] A second aspect of the present invention provides a composite positive electrode sheet, which is made by the above-mentioned preparation method.
[0046] The composite positive electrode sheet can be used as a positive electrode sheet of a battery, such as a sodium ion battery.
[0047] The third aspect of the present invention provides a method for preparing a sodium ion battery cell, comprising step S5 of making a negative electrode sheet 3, step S6 of assembling and forming, and step S7 of componentization; the assembly and forming includes step S61 of lamination and step S62 of assembly; the lamination method of step S61 is to obtain a bare battery cell by laminating the composite positive electrode sheet, negative electrode sheet, and diaphragm as described above.
[0048] More specifically, step S5 of making the negative electrode sheet includes the following steps:
[0049] Step S51, negative electrode homogenization: the biomass hard carbon material, the conductive agent SP, the binder sodium carboxymethyl cellulose (CMC), and the binder styrene butadiene rubber (SBR) are mixed uniformly in a mass ratio of (92-95): (1-4): (1-2): (1-3) to obtain a negative electrode slurry, and the solid content of the negative electrode slurry is controlled to be 40%-50%, and the viscosity is 3000mPa·s-6000mPa·s;
[0050] Step S52, negative electrode coating: coating the negative electrode slurry onto the negative electrode current collector 31, with the coating surface density controlled at 40 g / m 2 ~160g / m 2 , dried to form a negative electrode active material layer 32, and then the electrode sheet is rolled and cut into strips to form a negative electrode sheet 3.
[0051] More specifically, step S6 assembly molding includes the following steps:
[0052] Step S61: stacking the positive electrode sheets, negative electrode sheets and separators to obtain a bare battery cell, wherein there are 20 to 50 positive electrode sheets, 21 to 51 negative electrode sheets (it is necessary to ensure that the number of negative electrode sheets is one more than the number of positive electrode sheets), and the separator is a conventional PE-based film;
[0053] In step S62, after the aluminum-plastic film is punched, the bare cell is packaged in a shell, and the electrolyte is injected, and the shell is sealed again for soaking.
[0054] More specifically, step S7, the content conversion includes the following steps:
[0055] After a series of processes such as formation and capacity division, the battery cell 4 is obtained.
[0056] A fourth aspect of the present invention provides a sodium ion battery, the sodium ion battery comprising the aforementioned composite positive electrode sheet.
[0057] Through the above technical solutions, the present invention produces the following technical effects:
[0058] (1) The present invention coats the layered oxide and the polyanion material on the two plate surfaces of the mesh current collector respectively, and utilizes the mesh of the current collector to increase the contact area between the positive electrode slurry and the current collector, increase the contact area between the current collector and the positive electrode slurry per unit cross-sectional area, and improve the anchoring force and bonding force between the positive electrode material coating and the current collector.
[0059] (2) The present invention coats two different positive electrode materials on the two plate surfaces of the mesh current collector respectively, giving full play to the advantages of high specific capacity of layered oxides and long cycle life and high safety of polyanion materials, thereby improving battery performance.
[0060] (3) The present invention coats two different positive electrode materials on the two plate surfaces of the mesh current collector respectively, and adjusts the coating density according to the compaction performance of the two materials. Under the same rolling parameters, a suitable compaction density can be obtained, which can avoid the coating from falling off due to the different ductility of the two materials coated on the same side, and avoid the interface impedance between the coatings, thereby improving the battery cell capacity and rate performance.
[0061] (4) The technical solution of the present invention can reduce the resistivity of the positive electrode sheet and increase the battery life. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1 Schematic diagram of mesh current collector structure;
[0063] Figure 2 Schematic diagram of the composite positive electrode structure;
[0064] Figure 3 Schematic diagram of the structure of the negative electrode sheet;
[0065] Figure 4 A schematic diagram of the battery cell structure obtained by laminating composite positive electrode sheets;
[0066] Figure 5 The test results of the battery cell under 45℃ environment with 1C rate charge and discharge cycle.
[0067] 1 represents the mesh current collector; 11 represents the mesh on the surface of the current collector; 2 represents the composite positive electrode sheet; 21 represents the first coating; 22 represents the second coating; 3 represents the negative electrode sheet; 31 represents the negative electrode current collector, and 32 represents the negative electrode active material layer; 4 represents the battery cell; SOH represents the health status of the battery cell; Cycles represents the number of cycles. DETAILED DESCRIPTION
[0068] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0069] Example 1
[0070] Prepare the composite cathode sheet in the following steps:
[0071] Step S1, preparing positive electrode glue
[0072] Step S11, mixing N-methylpyrrolidone (NMP) and polyvinylidene fluoride (PVDF) in a mass ratio of 90:10, and stirring evenly;
[0073] Step S12, stirring for 15 minutes at an orbital speed of 10rpm and a rotation speed of 500rpm; scraping the wall and the paddle to scrape the PVDF stuck on the wall of the stirring tank and the stirring paddle into the solution; stirring for 12 hours at an orbital speed of 20rpm and a rotation speed of 1200rpm; adjusting the orbital speed to 10rpm and the rotation speed to 500rpm, evacuating for 1 hour, and controlling the vacuum degree to <-80KPa; controlling the viscosity of the glue to 1000mPa·s~4000mPa·s, and the solid content to 10%.
[0074] The positive electrode gel solution after stirring is transparent, without lumps or flocs.
[0075] Step S2, preparing positive electrode slurry A
[0076] Step S21, adding 1 / 2 to 2 / 3 of the positive electrode glue prepared in step S1 into a homogenization tank, and stirring for 30 minutes at a revolution speed of 10 rpm and a rotation speed of 500 rpm;
[0077] Step S22, adding SP carbon black conductive agent and carbon fiber conductive agent (VGCF) into a homogenization tank, stirring for 150 min at a revolution speed of 15 rpm and a rotation speed of 1800 rpm;
[0078] Step S23, putting the O3 layer oxygen material into a homogenization tank; controlling the mass ratio of the O3 layer oxygen material, polyvinylidene fluoride (PVDF), SP carbon black conductive agent, and carbon fiber conductive agent (VGCF) to be 95:3:1:1;
[0079] Step S24, adding the remaining 1 / 2 to 1 / 3 of the glue solution into the homogenization tank, stirring at a revolution speed of 10 rpm, a rotation speed of 500 rpm, and a stirring time of 15 min;
[0080] Step S25, scraping the wall and the paddle to scrape the material stuck on the wall of the stirring tank and the stirring paddle into the solution;
[0081] Step S26, stirring for 240 min at a revolution speed of 15 rpm and a rotation speed of 1800 rpm;
[0082] Step S27, adding NMP to adjust the slurry viscosity to 4000mPa·s to 8000mPa·s, and the solid content ranges from 50% to 60%;
[0083] Step S28, evacuate to remove bubbles, evacuate to a vacuum degree of less than -80 KPa, stir for 30 minutes at a revolution speed of 10 rpm and a rotation speed of 500 rpm to obtain positive electrode slurry A.
[0084] Step S3, preparing positive electrode slurry B
[0085] Step S31, adding the positive electrode glue in step S1 into a homogenization tank, stirring for 30 minutes at a revolution speed of 10 rpm and a rotation speed of 500 rpm;
[0086] Step S32, adding SP carbon black conductive agent and carbon fiber conductive agent (VGCF) into a homogenization tank, stirring for 180 min at a revolution speed of 15 rpm and a rotation speed of 1800 rpm;
[0087] Step S33, adding composite sodium ferric phosphate (NFPP) into a homogenization tank;
[0088] Step S34, adding the glue solution in step S1 into a homogenization tank, stirring for 15 minutes at a revolution speed of 10 rpm and a rotation speed of 500 rpm;
[0089] Step S35, scraping the wall and the paddle to scrape the material stuck on the wall of the stirring tank and the stirring paddle into the solution;
[0090] Step S36, stirring for 240 min at a revolution speed of 15 rpm and a rotation speed of 1800 rpm;
[0091] Step S37, adding NMP to adjust the slurry viscosity to 5000mPa·s to 8000mPa·s, and the solid content to 50% to 60%;
[0092] Step S38, evacuate to remove bubbles, evacuate to a vacuum degree of less than -80 KPa, stir for 30 minutes at a revolution speed of 10 rpm and a rotation speed of 500 rpm to obtain positive electrode slurry B.
[0093] Step S4, positive electrode coating
[0094] Step S41, coating the positive electrode slurry A on the first plate surface of the mesh current collector, the mesh current collector thickness is 8 μm, the mesh current collector mesh diameter is 5 μm, the mesh hole depth is ≤ 1 / 3 of the foil thickness, the mesh spacing is > 20 μm, and the coating surface density is controlled at 80 g / m 2 , drying to form a first coating, the thickness of the first coating is 50 μm;
[0095] Step S42: coating the positive electrode slurry B on the second plate surface of the mesh current collector with a coating surface density of 92 g / m 2 , drying to form a second coating;
[0096] Step S43, the electrode sheet is then rolled and cut into strips to form positive electrode sheets.
[0097] Example 2
[0098] Prepare the composite cathode sheet in the following steps:
[0099] Step S1, preparing positive electrode glue
[0100] Step S11, mixing N-methylpyrrolidone (NMP) and polyvinylidene fluoride (PVDF) in a mass ratio of 93:7, and stirring evenly;
[0101] Step S12, stirring for 15 minutes at an orbital speed of 10rpm and a rotation speed of 500rpm; scraping the wall and the paddle to scrape the PVDF stuck on the wall of the stirring tank and the stirring paddle into the solution; stirring for 6 hours at an orbital speed of 20rpm and a rotation speed of 1500rpm; adjusting the orbital speed to 10rpm and the rotation speed to 500rpm, evacuating for 1 hour, and controlling the vacuum degree to <-80KPa; controlling the viscosity of the glue to 1000mPa·s~4000mPa·s, and the solid content to 7%.
[0102] The positive electrode gel solution after stirring is transparent, without lumps or flocs.
[0103] Step S2, preparing positive electrode slurry A
[0104] Step S21, adding 1 / 2 to 2 / 3 of the positive electrode glue prepared in step S1 into a homogenization tank, and stirring for 30 minutes at a revolution speed of 10 rpm and a rotation speed of 500 rpm;
[0105] Step S22, adding SP carbon black conductive agent and carbon fiber conductive agent (VGCF) into a homogenization tank, stirring for 150 min at a revolution speed of 15 rpm and a rotation speed of 1800 rpm;
[0106] Step S23, putting the O3 layer oxygen material into a homogenization tank; controlling the mass ratio of the O3 layer oxygen material, polyvinylidene fluoride (PVDF), SP carbon black conductive agent, and carbon fiber conductive agent (VGCF) to be 94:3:2:1;
[0107] Step S24, adding the remaining 1 / 2 to 1 / 3 of the glue solution into the homogenization tank, stirring at a revolution speed of 10 rpm, a rotation speed of 500 rpm, and a stirring time of 15 min;
[0108] Step S25, scraping the wall and the paddle to scrape the material stuck on the wall of the stirring tank and the stirring paddle into the solution;
[0109] Step S26, stirring for 240 min at a revolution speed of 15 rpm and a rotation speed of 1800 rpm;
[0110] Step S27, adding NMP to adjust the slurry viscosity to 4000mPa·s to 8000mPa·s, and the solid content ranges from 50% to 60%;
[0111] Step S28, evacuate to remove bubbles, evacuate to a vacuum degree of less than -80 KPa, stir for 30 minutes at a revolution speed of 10 rpm and a rotation speed of 500 rpm to obtain positive electrode slurry A.
[0112] Step S3, preparing positive electrode slurry B
[0113] Step S31, adding the positive electrode glue in step S1 into a homogenization tank, stirring for 30 minutes at a revolution speed of 10 rpm and a rotation speed of 500 rpm;
[0114] Step S32, adding SP carbon black conductive agent and carbon fiber conductive agent (VGCF) into a homogenization tank, stirring for 150 min at a revolution speed of 15 rpm and a rotation speed of 1800 rpm;
[0115] Step S33, adding composite sodium ferric phosphate (NFPP) into a homogenization tank;
[0116] Step S34, adding the glue solution in step S1 into a homogenization tank, stirring for 15 minutes at a revolution speed of 10 rpm and a rotation speed of 500 rpm;
[0117] Step S35, scraping the wall and the paddle to scrape the material stuck on the wall of the stirring tank and the stirring paddle into the solution;
[0118] Step S36, stirring for 240 min at a revolution speed of 15 rpm and a rotation speed of 1800 rpm;
[0119] Step S37, adding NMP to adjust the slurry viscosity to 5000mPa·s to 8000mPa·s, and the solid content to 50% to 60%;
[0120] Step S38, evacuate to remove bubbles, evacuate to a vacuum degree of less than -80 KPa, stir for 30 minutes at a revolution speed of 10 rpm and a rotation speed of 500 rpm to obtain positive electrode slurry B.
[0121] Step S4, positive electrode coating
[0122] Step S41, coating the positive electrode slurry A on the first plate surface of the mesh current collector, the mesh current collector thickness is 15 μm, the mesh current collector mesh diameter is 8 μm, the mesh hole depth is ≤ 1 / 3 of the foil thickness, the mesh spacing is > 20 μm, and the coating surface density is controlled at 190 g / m 2, and dried to form a first coating having a thickness of 125 μm.
[0123] Step S42: coating the positive electrode slurry B on the second plate surface of the mesh current collector, with a coating surface density of 219 g / m 2 , drying to form a second coating;
[0124] Step S43, the electrode sheet is then rolled and cut into strips to form positive electrode sheets.
[0125] Example 3
[0126] Prepare the composite cathode sheet in the following steps:
[0127] Step S1, preparing positive electrode glue
[0128] Step S11, mixing N-methylpyrrolidone (NMP) and polyvinylidene fluoride (PVDF) in a mass ratio of 95:5, and stirring evenly;
[0129] Step S12, stirring for 15 minutes at an orbital speed of 10rpm and a rotation speed of 500rpm; scraping the wall and the paddle to scrape the PVDF stuck on the wall of the stirring tank and the stirring paddle into the solution; stirring for 12 hours at an orbital speed of 20rpm and a rotation speed of 1500rpm; adjusting the orbital speed to 10rpm and the rotation speed to 500rpm, evacuating for 1 hour, and controlling the vacuum degree to <-80KPa; controlling the viscosity of the glue to 1000mPa·s~4000mPa·s, and the solid content to 5%.
[0130] The positive electrode gel solution after stirring is transparent, without lumps or flocs.
[0131] Step S2, preparing positive electrode slurry A
[0132] Step S21, adding 1 / 2 to 2 / 3 of the positive electrode glue prepared in step S1 into a homogenization tank, and stirring for 30 minutes at a revolution speed of 10 rpm and a rotation speed of 500 rpm;
[0133] Step S22, adding SP carbon black conductive agent and carbon fiber conductive agent (VGCF) into a homogenization tank, stirring for 180 min at a revolution speed of 15 rpm and a rotation speed of 1800 rpm;
[0134] Step S23, putting the O3 layer oxygen material into a homogenization tank; controlling the mass ratio of the O3 layer oxygen material, polyvinylidene fluoride (PVDF), SP carbon black conductive agent, and carbon fiber conductive agent (VGCF) to be 93:3:2:2;
[0135] Step S24, adding the remaining 1 / 2 to 1 / 3 of the glue solution into the homogenization tank, stirring at a revolution speed of 10 rpm, a rotation speed of 500 rpm, and a stirring time of 15 min;
[0136] Step S25, scraping the wall and the paddle to scrape the material stuck on the wall of the stirring tank and the stirring paddle into the solution;
[0137] Step S26, stirring for 240 min at a revolution speed of 15 rpm and a rotation speed of 1800 rpm;
[0138] Step S27, adding NMP to adjust the slurry viscosity to 4000mPa·s to 8000mPa·s, and the solid content ranges from 50% to 60%;
[0139] Step S28, evacuate to remove bubbles, evacuate to a vacuum degree of less than -80 KPa, stir for 30 minutes at a revolution speed of 10 rpm and a rotation speed of 500 rpm to obtain positive electrode slurry A.
[0140] Step S3, preparing positive electrode slurry B
[0141] Step S31, adding the positive electrode glue in step S1 into a homogenization tank, stirring for 30 minutes at a revolution speed of 10 rpm and a rotation speed of 500 rpm;
[0142] Step S32, adding SP carbon black conductive agent and carbon fiber conductive agent (VGCF) into a homogenization tank, stirring for 180 min at a revolution speed of 15 rpm and a rotation speed of 1800 rpm;
[0143] Step S33, adding composite sodium ferric phosphate (NFPP) into a homogenization tank;
[0144] Step S34, adding the glue solution in step S1 into a homogenization tank, stirring for 15 minutes at a revolution speed of 10 rpm and a rotation speed of 500 rpm;
[0145] Step S35, scraping the wall and the paddle to scrape the material stuck on the wall of the stirring tank and the stirring paddle into the solution;
[0146] Step S36, stirring for 240 min at a revolution speed of 15 rpm and a rotation speed of 1800 rpm;
[0147] Step S37, adding NMP to adjust the slurry viscosity to 5000mPa·s to 8000mPa·s, and the solid content to 50% to 60%;
[0148] Step S38, evacuate to remove bubbles, evacuate to a vacuum degree of less than -80 KPa, stir for 30 minutes at a revolution speed of 10 rpm and a rotation speed of 500 rpm to obtain positive electrode slurry B.
[0149] Step S4, positive electrode coating
[0150] Step S41, coating the positive electrode slurry A on the first plate surface of the mesh current collector, the mesh current collector thickness is 17 μm, the mesh current collector mesh diameter is 10 μm, the mesh hole depth is ≤ 1 / 3 of the foil thickness, the mesh spacing is > 20 μm, and the coating surface density is controlled at 300 g / m 2 , drying to form a first coating, the thickness of the first coating is 50μm to 200μm.
[0151] Step S42: coating the positive electrode slurry B on the second plate surface of the mesh current collector with a coating surface density of 345 g / m 2 , drying to form a second coating;
[0152] Step S43, the electrode sheet is then rolled and cut into strips to form a composite positive electrode sheet.
[0153] Comparative Example 1:
[0154] The positive electrode slurry A prepared in Example 1 was coated on the two surfaces of the current collector, and the coating surface density was controlled at 80 g / m 2 , dried, and then the electrode is rolled and cut into strips to form positive electrode sheets.
[0155] Comparative Example 2:
[0156] The positive electrode slurry A prepared in Example 2 was coated on the two surfaces of the current collector, and the coating surface density was controlled at 180 g / m 2 , dried, and then the electrode is rolled and cut into strips to form positive electrode sheets.
[0157] Comparative Example 3:
[0158] The positive electrode slurry A prepared in Example 3 was coated on the two surfaces of the current collector, and the coating surface density was controlled at 300 g / m 2 , dried, and then the electrode is rolled and cut into strips to form positive electrode sheets.
[0159] The electrode sheet bonding force and electrode sheet resistivity of the positive electrode sheets of Examples 1 to 3 and Comparative Examples 1 to 3 were tested, and the results are shown in Tables 1 to 3. The bonding force of the coating of the embodiments is significantly higher than that of the comparative examples. The above results show that the present invention coats the layered oxide and the polyanion material on the two plate surfaces of the mesh current collector respectively, and utilizes the mesh of the mesh current collector to increase the contact area between the positive electrode slurry and the current collector, increase the contact area per unit volume of the current collector and the positive electrode slurry, and improve the anchoring force and bonding force between the positive electrode material and the foil.
[0160] It is difficult for a single positive electrode material to exert excellent comprehensive performance. The present invention coats two different positive electrode materials on the two plate surfaces of the mesh current collector respectively, giving full play to the advantages of high specific capacity of layered oxides and long cycle life and high safety of polyanion materials, thereby improving battery performance.
[0161] Two different positive electrode materials are coated on one side of the current collector in sequence. Since the two coatings cannot be completely fused, there is a large interface impedance between the two coatings, which affects the migration of electrons and ions, resulting in poor capacity and rate performance of the battery cell. Since the two coating materials are different, their density and ductility are different. During the later rolling, the top coating is prone to falling off or even falling off.
[0162] The present invention coats two different positive electrode materials on the two plate surfaces of the mesh current collector respectively, and adjusts the coating density according to the compaction performance of the two materials. Under the same rolling parameters, a suitable compaction density can be obtained, which can avoid the coating from falling off and falling off caused by the different elongation of the two materials on the same side, and can also reduce the interface impedance between the coatings, thereby improving the capacity and rate performance of the battery cell.
[0163] The lower the resistivity of the positive electrode material in the sodium ion battery, the higher the safety, the less energy loss during the charge and discharge process, and the longer the battery life. As shown in Table 3, the resistivity of the embodiment is significantly lower than that of the comparative example. The technical solution of the present invention can reduce the resistivity of the positive electrode sheet and improve the battery life.
[0164] Table 1 Test results of bonding strength of composite positive electrode sheet in Example
[0165] Sample serial number classification First coating adhesion (mN / mm) Second coating adhesion (mN / mm) Example 1 20.55 21.82 Example 2 22.25 21.96 Example 3 21.88 22.08 average value 21.56 21.95
[0166] Table 2 Comparative positive electrode sheet bonding test results
[0167] Sample classification Adhesion force (mN / mm) Comparative Example 1 16.23 Comparative Example 2 16.87 Comparative Example 3 17.15 average value 16.75
[0168] Table 3 Test results of positive electrode sheet resistivity
[0169]
[0170]
[0171] Example 4
[0172] Prepare sodium ion batteries according to the following steps:
[0173] Step S1, preparing positive electrode glue
[0174] Step S11, mixing N-methylpyrrolidone (NMP) and polyvinylidene fluoride (PVDF) in a mass ratio of 92:8, and stirring evenly;
[0175] Step S12, stirring for 15 minutes at an orbital speed of 10rpm and a rotation speed of 500rpm; scraping the wall and the paddle to scrape the PVDF stuck on the wall of the stirring tank and the stirring paddle into the solution; stirring for 12 hours at an orbital speed of 20rpm and a rotation speed of 1500rpm; adjusting the orbital speed to 10rpm and the rotation speed to 500rpm, evacuating for 1 hour, and controlling the vacuum degree to <-80KPa; controlling the viscosity of the glue to 1000mPa·s~4000mPa·s, and the solid content to 8%.
[0176] The positive electrode gel solution after stirring is transparent, without lumps or flocs.
[0177] Step S2, preparing positive electrode slurry A
[0178] Step S21, adding 1 / 2 to 2 / 3 of the positive electrode glue prepared in step S1 into a homogenization tank, and stirring for 30 minutes at a revolution speed of 10 rpm and a rotation speed of 500 rpm;
[0179] Step S22, adding SP carbon black conductive agent and carbon fiber conductive agent (VGCF) into a homogenization tank, stirring for 180 min at a revolution speed of 15 rpm and a rotation speed of 1800 rpm;
[0180] Step S23, putting the O3 layer oxygen material into a homogenization tank; controlling the mass ratio of the O3 layer oxygen material, polyvinylidene fluoride (PVDF), SP carbon black conductive agent, and carbon fiber conductive agent (VGCF) to be 93:3:2:2;
[0181] Step S24, adding the remaining 1 / 2 to 1 / 3 of the glue solution into the homogenization tank, stirring at a revolution speed of 10 rpm, a rotation speed of 500 rpm, and a stirring time of 15 min;
[0182] Step S25, scraping the wall and the paddle to scrape the material stuck on the wall of the stirring tank and the stirring paddle into the solution;
[0183] Step S26, stirring for 240 min at a revolution speed of 15 rpm and a rotation speed of 1800 rpm;
[0184] Step S27, adding NMP to adjust the slurry viscosity to 4000mPa·s to 8000mPa·s, and the solid content ranges from 50% to 60%;
[0185] Step S28, evacuate to remove bubbles, evacuate to a vacuum degree of less than -80 KPa, stir for 30 minutes at a revolution speed of 10 rpm and a rotation speed of 500 rpm to obtain positive electrode slurry A.
[0186] Step S3, preparing positive electrode slurry B
[0187] Step S31, adding the positive electrode glue in step S1 into a homogenization tank, stirring for 30 minutes at a revolution speed of 10 rpm and a rotation speed of 500 rpm;
[0188] Step S32, adding SP carbon black conductive agent and carbon fiber conductive agent (VGCF) into a homogenization tank, stirring for 180 min at a revolution speed of 15 rpm and a rotation speed of 1800 rpm;
[0189] Step S33, adding composite sodium ferric phosphate (NFPP) into a homogenization tank;
[0190] Step S34, adding the glue solution in step S1 into a homogenization tank, stirring for 15 minutes at a revolution speed of 10 rpm and a rotation speed of 500 rpm;
[0191] Step S35, scraping the wall and the paddle to scrape the material stuck on the wall of the stirring tank and the stirring paddle into the solution;
[0192] Step S36, stirring for 240 min at a revolution speed of 15 rpm and a rotation speed of 1800 rpm;
[0193] Step S37, adding NMP to adjust the slurry viscosity to 5000mPa·s to 8000mPa·s, and the solid content to 50% to 60%;
[0194] Step S38, evacuate to remove bubbles, evacuate to a vacuum degree of less than -80 KPa, stir for 30 minutes at a revolution speed of 10 rpm and a rotation speed of 500 rpm to obtain positive electrode slurry B.
[0195] Step S4, positive electrode coating
[0196] Step S41, coating the positive electrode slurry A on the first plate surface of the mesh current collector, the mesh current collector thickness is 17 μm, the mesh current collector mesh diameter is 10 μm, the mesh hole depth is ≤ 1 / 3 of the foil thickness, the mesh spacing is > 20 μm, and the coating surface density is controlled at 80 g / m 2 , drying to form a first coating, the thickness of the first coating is 50μm to 200μm.
[0197] Step S42: coating the positive electrode slurry B on the second plate surface of the mesh current collector with a coating surface density of 92 g / m 2 , drying to form a second coating;
[0198] Step S43, the electrode sheet is then rolled and cut into strips to form positive electrode sheets.
[0199] Step S5: making the negative electrode sheet comprises the following steps:
[0200] Step S51, negative electrode homogenization: the biomass hard carbon material, the conductive agent SP, the binder sodium carboxymethyl cellulose (CMC), and the binder styrene butadiene rubber (SBR) are mixed in a mass ratio of 92:2:2:2 to obtain slurry 3, and the solid content of slurry 3 is controlled to be 40% to 50%, and the viscosity is 3000mPa·s to 6000mPa·s.
[0201] Step S52, negative electrode coating: coating the negative electrode slurry C onto the negative electrode current collector, with the coating surface density controlled at 40 g / m 2 The negative electrode active material layer is formed and dried, and then the electrode sheet is rolled and cut into strips to form negative electrode sheets.
[0202] Step S6: assembly molding includes the following steps:
[0203] Step S61, lamination: the positive electrode sheet, the negative electrode sheet and the separator are laminated to obtain a bare battery cell, wherein there are 20 positive electrode sheets, 21 negative electrode sheets (it is necessary to ensure that the number of negative electrode sheets is 1 more than the number of positive electrode sheets), and the separator is a conventional PE base film;
[0204] Step S62, assembly: after the aluminum-plastic film is punched, the bare cell is packaged into a shell, and the electrolyte is injected, and the shell is sealed again for soaking.
[0205] Step S7, the content conversion includes the following steps:
[0206] After a series of processes including formation and capacity separation, a composite positive electrode sodium ion battery cell is obtained.
[0207] Example 5
[0208] Only the number of positive electrode lamination layers is increased to 30 based on Example 4.
[0209] Example 6
[0210] Only the number of positive electrode lamination layers is increased to 40 based on Example 4.
[0211] Example 7
[0212] Only the number of positive electrode lamination layers is increased to 50 based on Example 4.
[0213] Comparative Example 4
[0214] Take the positive electrode sheet prepared in Comparative Example 1, and stack 20 sheets according to the stacking method of Example 4 to make a battery cell.
[0215] Comparative Example 5
[0216] Take the positive electrode sheet prepared in Comparative Example 1, and stack 30 sheets according to the stacking method of Example 4 to make a battery cell.
[0217] Comparative Example 6
[0218] Take the positive electrode sheet prepared in Comparative Example 1, and stack 40 sheets according to the stacking method of Example 4 to make a battery cell.
[0219] Comparative Example 7
[0220] Take the positive electrode sheet prepared in Comparative Example 1, and stack 50 sheets according to the stacking method of Example 4 to make a battery cell.
[0221] The sodium ion battery cells of Examples 4 to 7 and the battery cells of Comparative Examples 4 to 7 were subjected to charge and discharge capacity tests at 1C rate at 25°C, and the results are shown in Table 4. When the number of positive electrode sheets is the same, the discharge capacity of the battery cells prepared in the Examples is higher than that of the Comparative Examples. The technical solution of the present invention can increase the capacity of sodium ion battery cells.
[0222] Table 4 Capacity test data of composite positive electrode sodium ion battery
[0223] Serial number Number of positive electrodes / piece 1C discharge capacity (Ah) Example 4 20 20.5 Example 5 30 30.8 Example 6 40 41.0 Example 7 50 51.3 Comparative Example 4 20 19.5 Comparative Example 5 30 29.3 Comparative Example 6 40 39.0 Comparative Example 7 50 48.8
[0224] The composite positive electrode sodium ion battery cells of Examples 4 to 7 and the battery cells of Comparative Examples 4 to 7 were subjected to a 1C rate charge and discharge cycle test at 45°C. The test results obtained were Figure 5 When the number of positive electrode sheets is the same, the capacity retention rate of the battery cell prepared in the embodiment is reduced by 20% after 2000 cycles; when the battery cell prepared in the comparative example is cycled 1100 times, the capacity retention rate of the battery cell is reduced by 20%. The technical solution of the present invention can increase the number of cycles and life of the sodium ion battery cell.
[0225] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.
Claims
1. A method for preparing a composite positive electrode sheet, characterized in that: The following steps are involved: Step S1, preparing a positive electrode glue solution, wherein the mass ratio of N-methylpyrrolidone to polyvinylidene fluoride in the positive electrode glue solution is (90-95): (5-10); Step S2, preparing positive electrode slurry A, wherein the mass ratio of O3 layer oxygen material, polyvinylidene fluoride, SP carbon black conductive agent, and carbon fiber conductive agent in the positive electrode slurry A is (93-95):3:(1-2):(1-2); Step S3, preparing positive electrode slurry B, wherein the mass ratio of polyanion material composite sodium iron phosphate, polyvinylidene fluoride, SP carbon black conductive agent, and carbon fiber conductive agent in the positive electrode slurry B is (90-95):3:(1-4):(1-3); Step S4, positive electrode coating, coating the positive electrode slurry A on the first plate surface of the mesh current collector (1), drying to form a first coating layer (21); coating the positive electrode slurry B on the second plate surface of the mesh current collector (1), drying to form a second coating layer (22); rolling and stripping the coated positive electrode sheet to form a composite positive electrode sheet (2).
2. The method for preparing the composite positive electrode sheet according to claim 1, characterized in that: The mesh current collector (1) has a thickness of 8 μm to 17 μm, a mesh (11) aperture of the mesh current collector (1) of 5 μm to 10 μm, a mesh (11) depth of ≤ 1 / 3 of the mesh current collector (1) thickness, and a mesh (11) spacing of > 20 μm.
3. The method for preparing the composite positive electrode sheet according to claim 2, characterized in that: The surface density of the first coating (21) is 80 g / m 2 ~300g / m 2 The thickness of the first coating (21) is 50 μm to 200 μm.
4. The method for preparing the composite positive electrode sheet according to claim 3, characterized in that: The surface density of the second coating (22) is 92 g / m 2 ~345g / m 2 .
5. The method for preparing the composite positive electrode sheet according to claim 1, characterized in that: The positive electrode glue has a viscosity of 1000mPa·s to 4000mPa·s and a solid content of 5% to 10%.
6. A composite positive electrode sheet, characterized in that: Made by any one of the methods of claims 1 to 5.
7. A battery cell, characterized in that: Including the composite positive electrode sheet as claimed in claim 1.
8. A sodium ion battery, characterized in that: Including the composite positive electrode sheet as claimed in claim 1.
